RANCANGAN BANGUN APLIKASI PEMESANAN SEMBAKO PADA TOKO MM ACING BERBASIS ANDROID: M-Commerce, Online Shopping, Android - Chrisna Putra, Rendy Rian; Setiawan Japriadi, Yohanes (JURNAL AKADEMIKA, 2018)
One of the activities that everyone is always doing in order to meet their needs is shopping, especially shopping in everyday life. As technology grows, shopping now can be done anywhere and anytime. Various online shopping activities by visiting the shop's website that offers goods have been commonly found lately. However, for people who have a busy activity, always mobile, shopping into a troublesome activity. In this study, developed software on smart phones based on Android. The goal is to answer the need for technology that makes it easy to shop in a practical and mobile. This research is more specialized in the development of Android operating system, because it has the appropriate technology and is available in various types and brands of smartphones.